The Valuation Channel of External Adjustment - Lee, Jaewoo (IMF Working Papers; Working Paper, 2009)
International financial integration has greatly increased the scope for changes in a country's net foreign asset position through the valuation channel, namely capital gains and losses on external assets and liabilities. We examine this valuation channel in a dynamic equilibrium portfolio model with international trade in equity. By separating asset prices and quantities, we can characterize the first-order dynamics of valuation effects and the current account in macroeconomic dynamics. Specifically, we disentangle the roles of excess returns, capital gains, and portfolio adjustment for consumption risk sharing when financial markets are incomplete.